Star wars: Doctor Aphra. Vol. 2, Doctor Aphra and the enormous profit - Gillen, Kieron (Marvel Worldwide, Inc., 2018)
"Aphra's back with a brand-new plan that's guaranteed to pay! There's just one teensy problem...it involves surrounding herself with some of the galaxy's biggest baddies. And they don't like the not-so-good doctor's tricks! Her mission to make quick credits by auctioning off an ancient Jedi artifact will start well...and end badly. And that's just when a dark figure from Aphra's past decides to make an appearance! Plus, a solo focus on Aphra's Wookiee shadow, Black Krrsantan! Find out why this beastly bounty hunter is as frightening as they say... and then some!"--provided by Amazon.com.